Assessment of the antimicrobial efficacy of complex therapy for persistent periodontitis during endodontic retreatment - I. A. Manukian; A. A. Adamchik; S. I. Risovannyi (Эндодонтия Today)
Aim. To evaluate the antimicrobial efficacy of endodontic retreatment of patients with destructive forms of persistent periodontitis using a combined approach to disinfection of the root canal system and a hyaluronic acid medication.Materials and methods. Group № 1 – endodontic retreatment with root canal disinfection by Hypochloran-3; group № 2 – the same, but for root canal disinfection, first "Hypochloran-3" was applied, and then photodynamic therapy using a 662 nm diode laser and a photosensitizer "ELOFIT®"; group № 3 – in addition to the manipulations carried out in group № 2, of the "Revident" medication was injected twice in the projection of the apical part of the causative tooth. Antibacterial efficacy was assessed according to the results of microbiological studies of biological samples taken before and 2 weeks after endodontic retreatment. The identification of microorganism colonies was carried out by mass spectrometry.Results. In patients with destructive forms of persistent periodontitis, both before and after root canals disinfection, Enterococcus faecalis ranked the first in terms of the frequency of detection in biological samples, Candida albicans the second, and Veillonella parvula the third. At the same time, before the treatment of root canals, the predominance (more than 80%) of polymicrobial associations with their participation was shown. After root canal treatment, the number of obtained microorganism isolates in groups 1-3 significantly decreased: by 60.0%, 74.3%, and 76.0%. Against this background, the share of strict anaerobes and microaerophiles in groups 1-3 decreased: by 60.6%, 81.3%, and 78.1%. The share of facultative anaerobes also significantly decreased by 59.7%, 79.7%, and 83.8%.Conclusions. Endodontic retreatment of patients with destructive forms of chronic periodontitis using combined disinfection of root canals both without and in combination with a hyaluronic acid medication is accompanied by a statistically significant reduction in species diversity, associations, and content of periodontal pathogenic microbiota.